1991
DOI: 10.1063/1.461153
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of orientational correlations and structural transitions in neat liquids

Abstract: The temperature dependence of depolarized light scattering intensity (DLSI) and nuclear magnetic resonance (NMR) chemical shift were measured for hexafluorobenzene in the temperature range from 10 to 63 °C. The DLSI curve is not monotone, consists of regions of different slope, and has a dip near 47 °C. The chemical shift curves also consists of different slope straight regions whose separation temperatures are coincident with anomalies on the DLSI curve. As DLSI is directly dependent on effective anisotropy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…As noted previously structural investigations on liquid benzene combining neutron diffraction and molecular dynamics simulations to study the evolution of the local ordering along the liquid−vapor coexistence curve (from temperatures close to the melting point up to the boiling point) have not been reported so far. Similarly, for hexafluorobenzene only measurements combining X-rays and neutron diffraction have been reported at room temperature. , The only available and indirect structural information concerning the temperature dependence of the local ordering for these two liquids has been obtained from the integrated intensity of depolarized light scattering. , It was found that a transition between local structures generated by dimers could be detected in both neat liquids. In contrast high-resolution stimulated Brillouin gain spectroscopy measurements show no evidence of “structural transition” …”
Section: Introductionmentioning
confidence: 99%
“…As noted previously structural investigations on liquid benzene combining neutron diffraction and molecular dynamics simulations to study the evolution of the local ordering along the liquid−vapor coexistence curve (from temperatures close to the melting point up to the boiling point) have not been reported so far. Similarly, for hexafluorobenzene only measurements combining X-rays and neutron diffraction have been reported at room temperature. , The only available and indirect structural information concerning the temperature dependence of the local ordering for these two liquids has been obtained from the integrated intensity of depolarized light scattering. , It was found that a transition between local structures generated by dimers could be detected in both neat liquids. In contrast high-resolution stimulated Brillouin gain spectroscopy measurements show no evidence of “structural transition” …”
Section: Introductionmentioning
confidence: 99%
“…It has been interpreted [24,25] as a dynamical transition within the liquid state. In fact, for most systems the findings at microscopic scales can be correlated with well-defined features in macroscopic thermodynamic quantities such as the specific heat [24,26] or even some transport properties such macroscopic shear viscosity and surface tension [27] which may show a noticeable curvature within a restricted range of temperatures.…”
Section: B Findings In Other Systemsmentioning
confidence: 99%
“…To this end, we would like to draw attention to the behavior observed in liquid Benzene (ref. 32) and Quinolene (ref. 33) where scattering experiments using traditional equilibration times (hours) found at temperatures close to crystallization an increased data scatter, but some peaks in the temperature dependencies of small-scale characteristics when the equilibration times were an order of magnitude longer.…”
Section: Introductionmentioning
confidence: 99%
“…The small size of the ordered nuclei and the expected relatively small differences in internal energies between these nuclei and the surrounding less-ordered material can create challenging condition for experimental observation of the equilibrium mosaic state, especially a necessity to use unusually long equilibration times for the mosaic to form. To this end, we would like to draw attention to the behavior observed in liquid Benzene [33] and Quinolene [34] where scattering experiments using traditional equilibration times (hours) found at temperatures close to crystallization an increased data scatter, but some peaks in the temperature dependencies of small-scale characteristics when the equilibration times were an order of magnitude longer.…”
mentioning
confidence: 99%